Differences in knowledge and attitudes of bride to be women before and after receiving health education about preconception nutrition through a WhatsApp group - Andriani, Evi; Sulistiawati, Rini; Utami, Rahayu Budi; Argaheni, Niken Bayu (Borneo Scientific Publishing, 2024)
Preconception health, particularly nutritional status, is a crucial factor in pregnancy preparation and is closely associated with maternal and neonatal outcomes. In West Kalimantan, the proportion of pregnant women at risk of Chronic Energy Deficiency (CED) reached 14.0% in 2017. Additionally, the prevalence of Low Birth Weight (LBW) increased from 3.20% in 2016 to 3.62% in 2017. This study aimed to determine differences in knowledge and attitudes of prospective brides before and after receiving health education on preconception nutrition delivered through a WhatsApp group in the West Pontianak Office of Religious Affairs (KUA) area. This study employed a quasi-experimental design with a one-group pretest–posttest approach. A total of 41 respondents were selected using consecutive sampling. Primary data were collected using a structured questionnaire. The results showed a significant improvement in both knowledge and attitudes of prospective brides after the health education intervention, with a p-value < 0.05 (p = 0.000). In conclusion, health education delivered through WhatsApp groups is effective in improving knowledge and attitudes regarding preconception nutrition among prospective brides.